2019
DOI: 10.2174/1386207322666190415101408
|View full text |Cite
|
Sign up to set email alerts
|

Invasive-noninvasive Sequential Ventilation for the Treatment of Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Background: The study aimed to evaluate the efficacy and safety of invasivenoninvasive sequential ventilation versus invasive ventilation in the treatment of Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD). Method: PubMed, Cochrane, Embase, Wanfang, CNKI, VIP database were searched by the index words to identify the qualified RCTs, and relevant literature sources were also searched. The latest research was conducted in June 2017. Relative Risks (RR), and Mean Difference (MD) along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…We found that mechanical ventilation time, invasive ventilation time, ICU stay and hospital stay in the study group were significantly shorter in the intervention group when compared to the conventional treatment group, thus indicating that noninvasive sequential ventilation therapy based on the use of an invasive ventilator can effectively shorten the mechanical ventilation time. This regimen was also shown to be conducive to the recovery of the disease, as confirmed by hospital stay data; these results were consistent with some previous reports [24,25]. Because non-invasive sequential ventilation therapy can ensure the stability of ventilation after invasive mechanical ventilation therapy; this strategy can improve a patient's respiratory failure symptoms, and parameters can be gradually adjusted according to the patient's actual condition to ensure that while reducing airway resistance, pulmonary surfactant consumption can also be reduced; in turn, this reduces ventilator oxygen consumption and shortens the overall duration of ventilation [26].…”
Section: Discussionsupporting
confidence: 92%
“…We found that mechanical ventilation time, invasive ventilation time, ICU stay and hospital stay in the study group were significantly shorter in the intervention group when compared to the conventional treatment group, thus indicating that noninvasive sequential ventilation therapy based on the use of an invasive ventilator can effectively shorten the mechanical ventilation time. This regimen was also shown to be conducive to the recovery of the disease, as confirmed by hospital stay data; these results were consistent with some previous reports [24,25]. Because non-invasive sequential ventilation therapy can ensure the stability of ventilation after invasive mechanical ventilation therapy; this strategy can improve a patient's respiratory failure symptoms, and parameters can be gradually adjusted according to the patient's actual condition to ensure that while reducing airway resistance, pulmonary surfactant consumption can also be reduced; in turn, this reduces ventilator oxygen consumption and shortens the overall duration of ventilation [26].…”
Section: Discussionsupporting
confidence: 92%
“…Although there was no significant difference in ventilation time and the length of ICU stay between the two groups, our study detected sequential MV was able to reduce the incidence of VAP and atelectasis, mainly due to the reduced time of invasive ventilation. A recent meta-analysis performed by Huang et al also assessed the safety of sequential MV versus conventional MV in the treatment of acute exacerbation of COPD (AECOPD) [ 15 ]. Their results showed the application of sequential MV at the pulmonary infection control window significantly reduced VAP incidence (RR: 0.20, 95% CI 0.16–0.26), mortality (RR: 0.38, 95% CI 0.26–0.55), reintubation rate (RR: 0.39, 95% CI 0.27–0.55), invasive ventilation time (MD: − 9.23, 95% CI − 10.65, − 7.82), total ventilation time (MD: − 4.91, 95% CI − 5.99, − 3.83), and the length of ICU stay (MD: − 5.10, 95% CI − 5.43, − 4.76).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no signi cant difference in ventilation time and the length of ICU stay between the two groups, our study detected SMV was able to reduce the incidence of VAP and atelectasis, mainly due to the reduced time of invasive ventilation. A recent meta-analysis performed by Huang et al also assessed the safety of SMV versus CMV in the treatment of acute exacerbation of COPD (AECOPD) [14].…”
Section: Discussionmentioning
confidence: 99%